Transformation and performance of granular sequence batch reactor under conventional organic loading rate condition - Zhong, Chen; Wang, Ya-qin; Lü, Jun-ping; Li, Yao-chen; Wang, Yong-jian; Zhu, Jian-rong (Journal of Central South University, 2014)
Laboratory experiments were conducted to investigate the transformation and performance of a granular sequence batch reactor (SBR) under the conventional organic loading rate (OLR) condition. Aerobic granules were successfully cultivated in a SBR by means of alternative feeding load combined with reducing settling time after 60 d operational period. Subsequently, the black fungal granules were presented in reactor because of the filamentous overgrowth on the surface of aerobic granules. A small amount of fungal granules had no effect on the performance of granular SBR. Aerobic granules completely vanished and fungal granules eventually became the dominant species in subsequent 90 d operation after granulation. The three-dimensional excitation emission matrix (EEM) spectra result shows that the extracellular polymeric substances (EPS) component in both granules has no much difference, whereas the content of EPS in fungal granules is higher than that in bacterial granules. Due to their low bioactivity, the chemical oxidation demand (COD) and NH 4 -N removal efficiencies gradually decrease from 90.4%–96.5% and 99.5% to 71.8% and 32.9% respectively while the fungal granules become dominant in the SBR.